Principles of construction and application of microwave systems for wireless energy transmission of ground and space basing - Gomozov, Andrei; Shokalo, Vladimir; Alvan Al-Samarai, Shamil Fadel; Gretskikh, Dmitry (Publishing House of Lviv Polytechnic National University, 2012)
The results of the investigations, carried out in Kharkiv National University of Radio Electronics, into the principles of construction of modern microwave systems for wireless energy transmission (WET) on the basis of a multipositional system of radiators (MSR) with focusing of single-stage discrete V-shaped multifrequency signals and a circular polarization rectenna, are presented. Викладено результати досліджень у Харківському національному університеті радіоелектроніки принципів побудови сучасних мікрохвильових систем безпровідної передачі енергії (БПЕ) на основі багатопозиційної системи випромінювачів (БСВ) з фокусeуванням одноступінчастих дискретних V-подібних багаточастотних сигналів і двошарової мікросмугової ректени з круговою поляризацією. Розглянуто два варіанти таких систем: для енергозабезпечення наземних об'єктів у важкодоступних районах і низько-орбітальних малогабаритних (НМ) космічних апаратів (КА).
Принципи побудови й застосування мікрохвильових систем безпроводової передачі енергії наземного й космічного базування
Keywords: wireless energy transmission; rectenna; multipositional system of radiators; electromagnetic radiation focusing; remote object; low-orbit space vehicle